2006
DOI: 10.3184/030823406777946789
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of monosubstituted calix[4]pyrroles in β position

Abstract: Through lithiation and electrophilic substitution of three calix [4]pyrroles, a series of new calix[4]pyrrole derivatives were synthesised. The derivatives were hydrolysed to produce acids and, under base catalysis, new esters were formed. Thus calix [4]pyrroles with an active functional group were obtained. The optimum reaction and purification conditions were investigated. The binding properties of the new derivatives with anions was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Despite the dominant position of sulfonated calixarenes among water-soluble supramolecular hosts, we found that examples bearing modifications on the upper rim such as the monosubstituted, trisulfonated calix[4]arenes exemplified by 2 (Figure ) have not been prepared synthetically or explored as supramolecular hosts. Recent work has highlighted the importance of selective functionalization of a variety of other macrocylic systems, such as calixpyrroles and cyclodextrins, in the tuning of binding properties and development of new technologies. , …”
mentioning
confidence: 99%
“…Despite the dominant position of sulfonated calixarenes among water-soluble supramolecular hosts, we found that examples bearing modifications on the upper rim such as the monosubstituted, trisulfonated calix[4]arenes exemplified by 2 (Figure ) have not been prepared synthetically or explored as supramolecular hosts. Recent work has highlighted the importance of selective functionalization of a variety of other macrocylic systems, such as calixpyrroles and cyclodextrins, in the tuning of binding properties and development of new technologies. , …”
mentioning
confidence: 99%